Electronic and optical properties of Mg3XN (X = P, As, Sb, Bi) antiperovskites: The GW/BSE approach. (1st November 2022) - Oyeniyi, Ezekiel
Abstract: Antiperovskites (APs) have several potential applications. Methods based on Density Functional Theory (DFT) have been applied to study the properties of APs. In this work, electronic and optical properties of Mg 3 XN (X = P, As, Sb, Bi) APs were investigated using the GW approximations and solution to the Bethe Salpeter Equation (BSE). The Mg 3 XN (X = P, As) were found to have direct band gaps while, Mg 3 XN (X = Sb, Bi) have indirect band gaps. The estimated G 0 W 0 /eVGW band gaps for Mg 3 PN, Mg 3 AsN, Mg 3 SbN, and Mg 3 BiN are 2.3328/2.6051, 2.1032/2.3620, 1.4156/1.6204 and 1.2917 eV/1.4760 eV, respectively. The inclusion of the spin–orbit coupling (soc) leads to a decrease in the G 0 W 0 /eVGW band gaps by about 15%/13% and 40%/33% for Mg 3 SbN and Mg 3 BiN, respectively. Optical properties obtained from the solution to BSE reveal that the APs could be promising materials for solar cell applications and optoelectronic devices. Highlights: The properties of Mg3 XN (X = P, As, Sb, Bi) antiperovskites were investigated using GW/BSE approach. Band gaps in the energy range 0.995–2.568 eV were predicted. Strong absorptions were observed in the ultraviolet–visible regions. The antiperovskites are potential materials for solar cells and optoelectronic devices.